MANAJEMEN KEBERSIHAN BERBASIS TANGGUNGJAWAB INDIVIDU DI SEKOLAH DASAR - Yudi Bachtiar (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2018)
School cleaning activities are generally something that no one wants. Most Indonesian people still assume that environmental hygiene is the work of janitors and helpers, not the collective responsibility of individuals. Not surprisingly, most schools in Indonesia have poor hygiene and health quality. This paper collects in-depth and comprehensive information from principals, teachers, and students at a private elementary school in the city of Purwakarta, West Java, regarding hygiene management in their schools. Unlike other schools, although it has two spacious and magnificent four-story buildings, this school does not have a single janitor. School cleanliness is truly a shared responsibility. In each day, dozens of teachers and hundreds of students clean up all parts of the school collectively in 15-20 minutes full of enthusiasm and awareness that cleanliness is a responsibility and part of their faith to Allah.